2011
DOI: 10.1590/s1808-86942011000500022
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of the auditory system: theoretical considerations

Abstract: Audi tory plasticity refers to the possibility of anatomical and/or functional changes in the system where transmission of auditory information takes place. The auditory system is often required in communication; it is important to learn how the auditory system reacts to stimuli in order to improve performance in individual communication of subjects with impaired hearing. Aim:To review the literature on auditory plasticity and the possibility and ability of plastic responses in the auditory system; also to rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
0
10
0
4
Order By: Relevance
“…Therefore the effect of training in new HA users (between 1 and 6 mo of use) compared to experienced HA users (over 2 yr of use) is largely unknown. One could hypothesize that new users, who have worn aids for more than 1 mo but less than 6 mo, may actually obtain greater benefit from such training than experienced HA users due to the reintroduction of portions of the auditory signal, which may provoke auditory plasticity (Kappel et al, 2011). This is an important issue to investigate as previous research has suggested that new HA users may benefit more from home-based AT than experienced HA users (Stecker et al, 2006).…”
Section: Description Of Listening and Communication Enhancement (Lace)mentioning
confidence: 99%
“…Therefore the effect of training in new HA users (between 1 and 6 mo of use) compared to experienced HA users (over 2 yr of use) is largely unknown. One could hypothesize that new users, who have worn aids for more than 1 mo but less than 6 mo, may actually obtain greater benefit from such training than experienced HA users due to the reintroduction of portions of the auditory signal, which may provoke auditory plasticity (Kappel et al, 2011). This is an important issue to investigate as previous research has suggested that new HA users may benefit more from home-based AT than experienced HA users (Stecker et al, 2006).…”
Section: Description Of Listening and Communication Enhancement (Lace)mentioning
confidence: 99%
“…The auditory plasticity may be understood as the capacity of reorganization of the nerve cells by means of a variation of input stimulus through enhancement and training. Thus, the auditory processing tests lead the speech pathologist to the more appropriate type of auditory training for each individual 13 . Due to the lack of studies in this area and to the importance of the comparative tests in the three moments of hearing aid fitting (on delivery, after a month of use and after the auditory training), this study aimed to verify the performance of elderly people in tests of auditory processing on the delivery of the hearing aid, after a month of using this device and after the auditory training.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the sooner severe or profound hearing loss is diagnosed without benefits with hearing aids, the child should be given the indication of a CI, since early exposure to auditory stimuli and incidental language allows the child to have a greater chance of developing the most complex auditory abilities and spoken language. The specialized literature evidenced a strong correlation between the development of auditory function and the period of CI surgery, with sensory deprivation time and age at implantation considered as one of the main predictors of success in the auditory habilitation and rehabilitation process (5)(6)(7)(8)(9)26) . This is because age is an intrinsic condition for the child, which ensures the normal development of the auditory cortex, necessary for the acquisition of auditory abilities, which are prerequisites for the development of spoken language (5)(6)(7)(8)(9)26) .…”
Section: Discussionmentioning
confidence: 99%
“…Cochlear implantation (CI) is an effective alternative for the treatment of hearing loss of severe or deep degrees, especially when performed in the first years of life, as it promotes the development of auditory abilities and, consequently, favors the acquisition of language spoken (5)(6)(7)(8) . Implantation in the first years of life allows the maturational process of the auditory cortex to occur properly as a result of electrical stimulation (5)(6)(7) .…”
Section: Introductionmentioning
confidence: 99%